3D Porous Structure in MXene/PANI Foam for a High‐Performance Flexible Pressure Sensor. Issue 48 (20th October 2022) - Yin, Tingting; Cheng, Yongfa; Hou, Yixin; Sun, Li; Ma, Yanan; Su, Jun; Zhang, Zhi; Liu, Nishuang; Li, Luying; Gao, Yihua
Abstract: The fields of electronic skin, man–machine interaction, and health monitoring require flexible pressure sensors with great sensitivity. However, most microstructure designs utilized to fabricate high‐performance pressure sensors require complex preparation processes. Here, MXene/polyaniline (PANI) foam with 3D porous structure is achieved by using a steam‐induced foaming method. Based on the structure, a flexible piezoresistive sensor is fabricated. It exhibits high sensitivity (690.91 kPa −1 ), rapid response, and recovery times (106/95 ms) and outstanding fatigue resistance properties (10 000 cycles). The MXene/PANI foam‐based pressure sensor can swiftly detect minor pressure and be further used for human activity and health monitoring. Abstract : Three‐dimensional porous MXene/PANI foam is achieved by using a steam‐induced foaming method and a flexible piezoresistive sensor is fabricated based on the structure. The mechanism, properties, and application of the device are studied.